Biofluid pumping and mixing by an AC electrothermal micropump embedded with a spiral microelectrode pair in a cylindrical microchannel. Issue 24 (20th September 2018) - Gao, Xiaobo; Li, Yuxiao
Abstract: In this paper, we numerically investigated a multifunctional AC electrothermal (ACET) micropump embedded with an asymmetric spiral microelectrode pair in a cylindrical microchannel for simultaneous pumping and mixing in high‐conductivity fluids, which makes the pump useful for biofluid applications. When an AC signal was applied to the asymmetric spiral electrode pair, the vortices induced on the electrode surfaces with centerlines along the corresponding spiral electrode length exhibit a spiral distribution, and the net flow in the cylindrical microchannel is generated by the ACET effect. The vorticity field distribution can explain the mechanism of simultaneous pumping and mixing. Because the vorticity field is inclined against the microchannel direction, vortices on top of the spiral electrodes can affect the ACET flow in the following two aspects at the same time: one is pumping the flow in the microchannel direction, and the other is mixing the samples by stirring the flow. We also determined that the geometric ratios of the electrode width to the gap or slant angle of the spiral electrodes can feasibly be used to control the relative strength of the pumping and mixing capabilities, and we achieved an optimal design that gives both desirable pumping and mixing efficiencies. This study shows that the spiral ACET micropump design can rapidly drive the high‐conductivity fluids and efficiently mix samples simultaneously. The numerical simulation of the spiral ACET micropump is of significant importance for practical, chemical and biological applications, and feasible fabrication techiniques should be experimentally investigated in future studies.